A New Proton Therapy Solution Provides Superior Cardiac Sparing Compared With Photon Therapy in Whole Lung Irradiation for Pediatric Tumor Patients - Sha, Xue; Duan, Jinghao; Lin, Xiutong; Zhu, Jian; Zhang, Ruohui; Sun, Tao; Wang, Hui; Meng, Xiangjuan; Yin, Yong (Frontiers in Oncology, 2021)
Objective: The intention of this research was to explore the advantage of cardiac sparing between photon and proton of WLI. Meanwhile, we proposed a new solution for cardiac sparing in proton techniques.Methods: Eleven patients with pediatric tumors and pulmonary metastasis who were treated with 12 Gy WLI (all treated with VMAT were retrospectively selected. Each patient was replanned with IMRT, HT, and two IMPT plans (IMPT-1 and IMPT-2). IMPT-1 considered the whole lung as PTV, utlizing the antero-posterior techniques (0/180°). IMPT-2 was a new proton solution which we proposed in this research. This approach considered unilateral lung as the PTV and 3 ipsilateral fields were designed for each lung. Then, IMPT-2 was generated by summing two unilateral lung plans. PTV coverage, conformity index (CI), homogeneity index (HI) and dose-volume statistics of cardiac and substructure, were assessed by means of the averages of each comparison parameter. Results: All treatment techniques achieved the target volume coverage required by clinical practice. HT yielded the best coverage and homogeneity for target structure. The excellent conformity index was observed in IMRT. For photon radiation therapy, HT plan afforded superior dose sparing for V5, V6, V7, V8, and Dmean of the heart, and Dmean of the right ventricle (RV). IMRT displayed the most notable dose reductions for V9,V10,V11,V12 of the heart, and Dmean of right atrium(RA). The VMAT plan was the least effective at heart and substructure. However, compared with photon radiation therapy, IMPT-1 did not showed advantage for heart protection in this study. Interestingly, IMPT-2 provided the significantly superiority in cardiac sparing, including the maximum dose sparing for V5, V6, V7, V8, V9 and Dmean of the heart, and Dmean of the RA, RV, left atrium (LA) and left ventricle (LV) .Conclusions: Considering the complex anatomical relation between target volumes and organs at risk (OARs), IMPT can provide dose advantage for organs located at outside of the target area rather than within or be surrounded by it. It is hoped that advances in PT plan designing will lead to further improvement in radiotherapy approaches and provide the best choice of treatment for the individual patient.